CoMa 2013 Safeguarding Image Collections. - Arijs, Hilke (Newcastle upon Tyne : Cambridge Scholars Publishing, 2014)
This book presents the proceedings of the ""CoMa 2013: Safeguarding Image Collections"" international conference held in Brussels, on 31 October 2013, and offers the reader not only a wide variety of subjects relating to the preservation of image collections, but also an overview of the different professions and practices involved in the preservation of photographic heritage. The proceedings contain some practical examples illustrating how CEN regulations and generally accepted standards can b...
COMBINING SCENOGRAPHY AND PRESERVATIONCONSERVATION OF CELLULOSE ACETATEPHOTOGRAPHIC NEGATIVES; ON THE MARKING OF PHOTOGRAPHY; THE CHARACTERIZATION AND CONSERVATIONTREATMENT OF AN ALBUMEN PHOTOGRAPHUSING ADVANCED IMAGING TECHNIQUESAND NOVEL REINTEGRATION METHODS; Part IV; CONSERVATION AND DIGITIZATIONOF NITRATE FILMS AT THENATIONAL FILM ARCHIVE IN POLAND; SUSTAINABLE RE-USE OFDIGITIZED ARCHIVAL CONTENT; FROM DUST TO DISPLAY; Part V; SAFEGUARDING IMAGE COLLECTIONS,WHY AND FOR WHOM?; LIST OF CONTRIBUTORS; INDEX
Description based upon print version of record.
Keywords: Photography -- History; Photography -- Techniques; Photography; Photographs -- Conservation and restoration -- Congresses; Photograph collections -- Conservation and restoration -- Congresses; COMPUTERS / Digital Media / Photography; PHOTOGRAPHY / Reference; TECHNOLOGY & ENGINEERING / Imaging Systems; Electronic books